Penerapan E-Government Menggunakan Quick Response Code Indonesian Standard (QRIS) pada Pembayaran Pajak Bumi Bangunan di Kota Bandung. - Ajeng Nofita; Slamet Usman Ismanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study analyzes the implementation of the Quick Response Code Indonesian Standard (QRIS) as a payment method for Land and Building Tax (PBB) in Bandung City. The Bandung City Government, through the Regional Revenue Agency (Bapenda), adopted QRIS technology to enhance efficiency, transparency, and accessibility in tax payments. The use of QRIS facilitates taxpayers to make payments without visiting the payment office, reduces administrative costs, and enables real-time monitoring of tax receipts. This research method involves interviews with taxpayers and tax officials, as well as data collection from observations and related sources. The results indicate that QRIS speeds up the payment process, improves administrative efficiency, and reduces costs. Despite its ease of use, the adoption rate of QRIS remains low at only 0.70% in the first year. To increase adoption, more socialization and training on the benefits and usage of QRIS are needed. Based on E-Government theory, the implementation of QRIS at Bapenda Kota Bandung shows that leadership, information infrastructure, information management, and socialization are key to improving the quality of public services and budget management.